Efficacy of Cytokine Hemoadsorption with Efferon CT in Severe Acute Pancreatitis - V. V. Kiselev; M. S. Zhigalova; E. V. Klychnikova; S. I. Rey; P. A. Yartsev (Общая реаниматология, 2024)
The aim of the study was to evaluate the eﬀect of cytokine hemoadsorption on clinical manifestations and laboratory parameters in patients with severe acute pancreatitis (SAP).Materials and methods. The single-center, observational, controlled pilot study included 34 patients, 25 men (73.4%) and 9 women (26.4%), treated for severe acute pancreatitis (SAP) at the N. V. Sklifosovsky Emergency Care Research Institute from May 2022 to August 2023 (ClinicalTrials.gov ID NCT05695001). The mean age of the patients was 42.7±12.6 years. Participants were divided into two groups. In the main group (8 men and 1 woman], mean age 37.2±9.4 years), standard care was supplemented by selective cytokine hemoadsorption (SCH) and renal replacement therapy (RRT) using continuous veno-venous hemoﬁltration (CVVH) in the ﬁrst 72 hours after the onset of abdominal pain syndrome (APS). In the control group (N=25, 18 men and 7 women], mean age 44.7±13.2 years), patients were managed similarly except for SCH.Results. After 24 hours in the ICU, the study group had signiﬁcantly lower levels of lactate (P=0.045) and IL-6 (P<0.001) than the control group. Lactate and IL-6 concentrations remained signiﬁcantly diﬀerent between groups at 72 hours (P<0.001 and P<0.05, respectively). ICU stay was signiﬁcantly shorter in the study group, with a median of 6 days [95% CI, 4–25] before transfer to the general ward, whereas patients in the control group spent 37 days [95% CI, 22–73] in the ICU (P<0.001).Conclusion. CVVH is an eﬀective method of extracorporeal detoxiﬁcation in the management of SAP, but it is less speciﬁc than cytokine adsorption in terms of elimination of proinﬂammatory markers. The data obtained provide suﬃcient evidence to consider the combination of these two modalities as the most eﬀective approach for the management of SAP.